The Impact Of Gadget Use On Online Learning During The Covid-19 Pandemic On The Character Of Elementary School Students - Al Ihwanah; Tutut Handayani; Nur Laily (Sean Institute, 2022)
The purpose of this study is to analyze how the impact of using gadgets towards the character of students, especially elementary school students in the era of the covid 19 pandemic. The formation of this character can be shown by students to become better individuals. Elementary school age children are more vulnerable to being able to imitate what is seen in the digital world. Online learning through gadgets in the era of the covid-19 pandemic is one of the methods used by the government so that education and learning in Indonesia can be carried out. Students in everyday life always rely on gadgets. The use of gadgets during online learning has an impact, both positive and negative. This study uses a qualitative method. Data collection techniques are observation, interviews, and documentation. The subjects of this study were elementary school students. Based on the results of the study, the positive impacts of using gadgets are creative, independent, curious, and communicative friendly. The negative impacts include dishonesty, lack of discipline, lack of care, lack of responsibility, lack of religion, and unwillingness to work hard.